Getting From Here to There: Maine’s Elder Transportation Challenge - Freund, Katherine (Maine Policy Review, 2015)
Surveys and studies have repeatedly pointed out the problem of transportation for elders in Maine. Katherine Freund reviews Maine transportation studies and policy and suggests that the solution lies in developing private transportation alternatives that are supported by technology and by appropriate public policies.